Changes in five‐year survival for people with acute leukaemia in South Australia, 1980–2016. Issue 6 (16th February 2022) - Beckmann, Kerri; Kearney, Brendon J; Yeung, David; Hiwase, Devendra; Li, Ming; Roder, David M
Abstract: Objectives: To examine population changes in 5‐year survival for people in South Australia diagnosed with acute leukaemia during 1980–2016, by socio‐demographic characteristics. Design, setting: Retrospective analysis of South Australian Cancer Registry data for the period 1980–2016. Participants: All South Australian residents diagnosed with primary acute lymphoblastic leukaemia (ALL) or acute myeloid leukaemia (AML) during 1980–2016. Main outcome measures: 5‐year disease‐specific survival and disease‐specific mortality. Results: Crude 5‐year disease‐specific survival was 58% (95% CI, 54–61%) for the 1035 people diagnosed with ALL during 1980–2016, and 18% (95% CI, 17–20%) for the 2814 people diagnosed with AML. Survival improved steadily across the study period: from 44% (95% CI, 35–52%) for people with ALL diagnosed during 1980–1984 to 69% (95% CI, 63–75%) for those diagnosed during 2010–2016; and from 9% (95% CI, 5–15%) to 23% (95% CI, 20–26%) for people diagnosed with AML. Disease‐specific mortality increased with age, but was not influenced by socio‐economic status or remoteness of residence. After adjusting for other factors, rates of change in risk of leukaemia‐related death were greater for younger than older patients with ALL (for interaction: P = 0.004) or AML ( P = 0.005), but were not significantly influenced by socio‐economic status or remoteness. Conclusion: Five‐year survival for people with acute leukaemia in South Australia continuously improved during 1980–2016, and socio‐economic status and remoteness did not influence survival. It improved markedly for younger patients (under 50 years of age). However, survival is still relatively poor, especially for people over 50 years with AML.